Looking through the lens of stigma: Understanding and anticipating concerns about the responsible development and use of psychiatric electroceutical interventions (PEIs) - Sandra Cai Chen; Robyn Bluhm; Eric D. Achtyes; Aaron M. McCright; Laura Y. Cabrera (SSM - Mental Health, 2023)
Psychiatric electroceutical interventions (PEIs) show promise for treating depression, but few studies have examined stakeholders' views on them. Using interview data and survey data that analyzed the views of psychiatrists, patients, caregivers, and the general public, a conceptual map was created to represent stakeholders’ views on four PEIs: electroconvulsive therapy (ECT), repetitive transcranial magnetic stimulation (TMS), deep brain stimulation (DBS), and adaptive brain implants (ABIs). Stigma emerged as a key theme connecting diverse views, revealing that it is a significant factor in the acceptance and usage of PEIs. Stigma not only discourages seeking mental health services for depression but also inhibits the acceptance of PEIs. Addressing the pervasive and complex effects of stigma highlights the need to change societal attitudes toward mental illnesses and their treatments and to provide support to patients who may benefit from these interventions. The map also demonstrates the value of conceptual mapping for anticipating and mitigating ethical considerations in the development and use of PEIs.